Anticancer properties of sulforaphane: current insights at the molecular level - Asif Ali, Muhammad; Khan, Noohela; Kaleem, Nabeeha; Ahmad, Waqas; Alharethi, Salem Hussain; Alharbi, Bandar; Alhassan, Hassan H.; Al-Enazi, Maher M.; Razis, Ahmad Faizal Abdull; Modu, Babagana; Calina, Daniela; Sharifi-Rad, Javad (Frontiers in Oncology, 2023)
Sulforaphane (SFN) is an isothiocyanate with multiple biomedical applications. Sulforaphane can be extracted from the plants of the genus Brassica. However, broccoli sprouts are the chief source of sulforaphane and are 20 to 50 times richer than mature broccoli as they contain 1153mg/100g. SFN is a secondary metabolite that is produced as a result of the hydrolysis of glucoraphanin (a glucosinolate) by the enzyme myrosinase. This review paper aims to summarize and understand the mechanisms behind the anticancer potential of sulforaphane. The data was collected by searching PubMed/MedLine, Scopus, Web of Science and Google Scholar. This paper concludes that sulforaphane provides cancer protection through the alteration of various epigenetic and non-epigenetic pathways. It is a potent anticancerous phytochemical that is safe to consume with minimal side effects. However, there is still a need for further research regarding SFN and the development of a standard dose.